Perbandingan Program Zakat Produktif antara BAZNAS dan LAZISMU Kota Surakarta - Lukmanul Hakim; Azhar Alam; M. Mus’ab At-Thariq; Dedi Junaedi; M. Rizal Arsyad (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
This study aims to compare the productive zakat program between Baznas Surakarta City and Lazismu Surakarta City and to study the disadvantages and advantages of these zakat institutions in distributing productive zakat. This research uses descriptive qualitative research methods. Sources of data obtained by in-depth interviews with representatives of zakat and mustahik institutions. Sources of data obtained through literature related to productive zakat. The results of this study indicate that Baznas and Lazismu Surakarta City have differences between the distribution of productive zakat; mustahik criteria; muzakki criteria; zakat fund collection; distribution of zakat funds: and assistance to mustahik. The types of assistance given to the mustahik are both in the form of business capital and means of production. The productive zakat program run by the two zakat institutions has been very effective in helping and increasing the income of the previous mustahik, and some mustahik have become hypocrites. The difference between the two zakat institutions is based on the background of the establishment and the Standard Operating Procedure (SOP) of zakat institutions, so that it becomes the hallmark of the two institutions in the practice of productive zakat funds to mustahik; become a reference for muzakki to distribute their zakat; and guide mustahiks to choose zakat institutions that are suitable for their business.